2013
DOI: 10.1162/artl_a_00084
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Computation of Multi-Gaited Robot Locomotion Based on Free Vibration

Abstract: In recent years, there has been increasing interest in the study of gait patterns in both animals and robots, because it allows us to systematically investigate the underlying mechanisms of energetics, dexterity, and autonomy of adaptive systems. In particular, for morphological computation research, the control of dynamic legged robots and their gait transitions provides additional insights into the guiding principles from a synthetic viewpoint for the emergence of sensible self-organizing behaviors in more-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 39 publications
1
26
0
8
Order By: Relevance
“…Basically, the vibration induces random motions of the body, which then selects a preferred direction based on the anisotropic friction. This locomotion was well described by a slip-stick model [136]: in this representation, the friction force was reduced due to the rotation of the mass, which pushed toward (or off ) the ground during half-rotation. Within this category, we can find beam-like robots that exploit resonance frequency to save energy [137], adaptable balloon robots that can vary their vibration frequency and their shape to adapt to different substrates [138], worm-like robots capable of vibration-based locomotion or two-anchor crawling [139,140] and a multi-gait robot that is also capable of jumping [141].…”
Section: Alternative Modes Of Locomotionmentioning
confidence: 92%
“…Basically, the vibration induces random motions of the body, which then selects a preferred direction based on the anisotropic friction. This locomotion was well described by a slip-stick model [136]: in this representation, the friction force was reduced due to the rotation of the mass, which pushed toward (or off ) the ground during half-rotation. Within this category, we can find beam-like robots that exploit resonance frequency to save energy [137], adaptable balloon robots that can vary their vibration frequency and their shape to adapt to different substrates [138], worm-like robots capable of vibration-based locomotion or two-anchor crawling [139,140] and a multi-gait robot that is also capable of jumping [141].…”
Section: Alternative Modes Of Locomotionmentioning
confidence: 92%
“…When the robot is deflated, however, the rotor must be spun backwards (moving backwards at its highest point) to produce forward motion. This phenomenon has been previously described and analyzed in further detail by Reis et al (2013). Figure 4 shows Fourier transforms of vertical acceleration data from an accelerometer mounted on the robot during locomotion on the two assessed terrains (hard floor and sand) and in two different states (inflated and deflated).…”
Section: Gaitsmentioning
confidence: 63%
“…The robot's ability to move is well described by a stick-slip locomotion model that has previously been used to describe and simulate other hopping and vibrating robots (Rubenstein et al, 2012;Reis et al, 2013;Reis and Iida, 2014). The mechanics by which rotation of an out-of-balance mass may be transformed into locomotion is described below.…”
Section: Stick-slip Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Inspired by the experiment with horses [3], a study [24] suggested that there is a correspondence between the gaits of actual horses and the free vibration modes of a horse model. In this paradigm, some authors [25,26] proposed a methodology to control the whole body motion based on free vibration. Their robots had a simple elastic body and a vibration motor that achieves an energy-efficient hopping motion by exploiting the free vibration mode of the robot body.…”
Section: Introductionmentioning
confidence: 99%